Survivor engagement: Experience with an advocacy-based model in Washington, D.C. - O'Connor, Seini; Barron, Andrea; Byimana, Léonce; Isley, Jennifer; Patel, Sheetal; Dhital, Yadhu; Bazaz, Nouf (Torture Journal, 2023)
Introduction: As an IRCT member organization supporting survivors of torture, the Torture Abolition and Survivor Support Coalition (TASSC) International places survivor engagement at the core of their work, aiming to provide safe and inclusive spaces for survivors to speak out and take meaningful action to prevent torture. This article describes TASSC’s model for engaging survivors in advocacy and presents evidence on the personal impacts such engagement can have. Method: Each year from 2016-2019, TASSC administered a simple survey with questions for survivors to complete after their annual “Advocacy Day” in Washington D.C. Quantitative and qualitative data was collected to inform internal service provision and the design of future events. Results: Across the four years a total of 140 survivors and compatriot human rights advocates participated in the annual Advocacy Day, and a majority completed the surveys. In their survey responses, survivors agreed they had many positive thoughts and feelings after advocacy. Their reported positive experiences included a sense of being listened to and heard by an understanding and responsive audience, the power of feeling part of a group that was speaking out on behalf of themselves and others, and a sense of motivation and hopefulness for the future. Discussion: Although undertaken primarily to inform internal processes, TASSC’s surveys with survivors who engaged in advocacy shed light on the potential value of well-designed advocacy experiences. Consistent with past research, survivors reported strong motivations around and compelling benefits from participating, despite the challenges that the deeply personal nature of their engagement could present. This feedback suggests TASSC has a strong model that could be replicated elsewhere, but it would be beneficial to further investigate the experiences of survivors engaging in advocacy in other country settings.